2014
DOI: 10.1111/bjop.12068
|View full text |Cite
|
Sign up to set email alerts
|

Reach out to one and you reach out to many: Social touch affects third‐party observers

Abstract: Casual social touch influences emotional perceptions, attitudes, and behaviours of interaction partners. We asked whether these influences extend to third-party observers. To this end, we developed the Social Touch Picture Set comprising line drawings of dyadic interactions, half of which entailed publicly acceptable casual touch and half of which served as no-touch controls. In Experiment 1, participants provided basic image norms by rating how frequently they observed a displayed touch gesture in everyday li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 72 publications
4
30
0
Order By: Relevance
“…This finding shows that third-party observers of touch are affected by the social experience of touch observation and that social exchange of touch is deemed pleasant in the eye of the observer. Our study is in line with recent findings showing that photos containing touch are considered more positive and exciting compared to photos without touch (Schirmer et al, 2015) and further indicates that the perception of social touch can induce feelings in an observer who is not part of the touch itself.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding shows that third-party observers of touch are affected by the social experience of touch observation and that social exchange of touch is deemed pleasant in the eye of the observer. Our study is in line with recent findings showing that photos containing touch are considered more positive and exciting compared to photos without touch (Schirmer et al, 2015) and further indicates that the perception of social touch can induce feelings in an observer who is not part of the touch itself.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, social psychology literature shows that gestures of touch have an impact on the attitudes and behaviors of another individual and that social touch can enhance a positive evaluation of the toucher (Crusco & Wetzel, 1984;Fisher, Rytting, & Heslin, 1976). It has recently been reported that interactions involving touch are considered more positive and exciting than are interactions with no touch (Schirmer et al, 2015), indicating that third party observers of touch may possibly share the touch recipient's social experiences.…”
mentioning
confidence: 99%
“…(Right) Compared to no-touch interactions, tactile interactions are perceived as more positive and arousing. Images taken from the Social Touch Picture Set [108]. …”
Section: Figurementioning
confidence: 99%
“…These studies therefore only address a very small part of "affective touch" since humans use much more complex and varied interactions to express affective intentions (both positive and negative) by touch. A wider range of more complex interpersonal affective touch events has so far only been addressed in studies using static images (for example, using pictures of kissing, hugging, and hitting as stimuli: (15)(16)(17)(18). However, there has been 1 Bänziger T, Scherer KR.…”
Section: Introductionmentioning
confidence: 99%